Obstacles to development in the field of education (Journal Of Educational and Psychological Researches, 2017)
Education is the most powerful and important weapon in fighting poverty and unemployment because it provides students with new skills that appropriate the new market requirements and fair distribution of natural resources. It also transfers knowledge, skills, and ethics over generations. Education aims to create effective leaders who go under training and rehabilitation process, create a new human and instill faith, generate the creativity and innovation, and keep abreast with scientific process, updating curriculum, and finally, applying the technical education